Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2147/cmar.s238373
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Noncoding RNA <em>ZFPM2-AS1</em> Enhances the Malignancy of Cervical Cancer by Functioning as a Molecular Sponge of microRNA-511-3p and Consequently Increasing FGFR2 Expression</p>

Abstract: Purpose: A long noncoding RNA called ZFPM2 antisense RNA 1 (ZFPM2-AS1) has been verified as a key modulator in multiple human cancer types. Nonetheless, the expression and functions of ZFPM2-AS1 in cervical cancer remain poorly understood. Therefore, our purpose was to characterize the expression pattern, clinical value, and detailed roles of ZFPM2-AS1 in cervical cancer. Methods: Reverse-transcription quantitative PCR was carried out to measure ZFPM2-AS1 expression in cervical cancer. A Cell Counting Kit-8 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Our study further demonstrated that the BMSC-derived EVs could transfer miR-375 to cervical cancer cells and consequently acted as antioncogene in cervical cancer cells, evidenced by promoted cell apoptosis and inhibited cell migration and invasion. Importantly, the inhibited proliferation, migration, and invasion are significant indicators for the amelioration of cervical cancer [ 30 , 31 ]. Moreover, the present study clarified that BMSC-derived EV-incorporated miR-375 could ameliorate cervical cancer progression in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Our study further demonstrated that the BMSC-derived EVs could transfer miR-375 to cervical cancer cells and consequently acted as antioncogene in cervical cancer cells, evidenced by promoted cell apoptosis and inhibited cell migration and invasion. Importantly, the inhibited proliferation, migration, and invasion are significant indicators for the amelioration of cervical cancer [ 30 , 31 ]. Moreover, the present study clarified that BMSC-derived EV-incorporated miR-375 could ameliorate cervical cancer progression in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…ZFPM2-AS1 has also been shown to promote metastasis and proliferation, as well as inhibit renal cell cancer apoptosis by targeting miR-137 ( Liu et al, 2019 ). Additionally, ZFPM2-AS1 can promote NSCLC progression via the miR-511-3p/AFF4 and miR-18b-5p/VMA21 pathways ( Li et al, 2020 ; Xue et al, 2020 ), and enhance the malignancy of cervical cancer by sponging microRNA-511-3p ( Dai et al, 2020 ). By upregulating TRAF4, ZFPM2-AS1 facilitates cell proliferation in both esophageal squamous cell carcinoma and small cell lung cancer ( Sun & Wu, 2020 ; Yan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, lncRNA ZFPM2-AS1 promotes lung adenocarcinoma progression by interacting with UPF1 to destabilize ZFPM2 [ 40 ]. Recently, researchers reported that the cancer-promoting activities of ZFPM2-AS1 were mediated by the MIF–p53 signaling pathway in gastric cancer, by the miR-18b-5p–VMA21 axis in lung adenocarcinoma, by miR-137 in renal cell cancer, and by miRNA-511-3p and consequently increasing the FGFR2 expression in cervical cancer [ 36 39 , 41 ]. ZFPM2-AS1 was previously identified as a prognostic lncRNA in a TCGA lncRNA-based prognostic signature investigation in HCC patient prognoses [ 42 ].…”
Section: Discussionmentioning
confidence: 99%